Cambrian Chordates and Vetulicolians - McMenamin, Mark A. S. (Geosciences (Basel), 2019)
Deuterostomes make a sudden appearance in the fossil record during the early Cambrian. Two bilaterian groups, the chordates and the vetulicolians, are of particular interest for understanding early deuterostome evolution, and the main objective of this review is to examine the Cambrian diversity of these two deuterostome groups. The subject is of particular interest because of the link to vertebrates, and because of the enigmatic nature of vetulicolians. Lagerstätten in China and elsewhere have dramatically improved our understanding of the range of variation in these ancient animals. Cephalochordate and vertebrate body plans are well established at least by Cambrian Series 2. Taken together, roughly a dozen chordate genera and fifteen vetulicolian genera document part of the explosive radiation of deuterostomes at the base of the Cambrian. The advent of deuterostomes near the Cambrian boundary involved both a reversal of gut polarity and potentially a two-sided retinoic acid gradient, with a gradient discontinuity at the midpoint of the organism that is reflected in the sharp division of vetulicolians into anterior and posterior sections. A new vetulicolian (Shenzianyuloma yunnanense nov. gen. nov. sp.) with a laterally flattened, polygonal anterior section provides significant new data regarding vetulicolians. Its unsegmented posterior region (‘tail’) bears a notochord and a gut trace with diverticula, both surrounded by myotome cones.